Effect of Applied Load Way on Thermal-structural Temperature Field of Wet Clutch - Zhigang Zhang; Yao Chen; Xiaohui Shi; Bin Ye; Sheng Yin (Jixie chuandong)
Based on the actual structure and work conditions of wet multi-disc clutch, a finite element analysis model of wet clutch is established by using Abaqus. The temperature field of friction pairs in wet clutch is analyzed by the direct thermal structure coupling method，and the influence of the applied load way of piston in wet clutch on the temperature field of friction pairs is studied. The results show that the applied load way has an important effect on the temperature field of separator plate，and the most obvious effect is on the separator plate which is directly affected by the piston. The maximum temperature under partial load way is higher than that under uniform load way and the maximum temperature under partial load way appears earlier. The bandwidth of high temperature on separator plate is narrower and the radial temperature gradient is larger which under partial load way.